Axillary Lymph Node Dissection Does Not Improve Post-mastectomy Overall or Disease-Free Survival among Breast Cancer Patients with 1-3 Positive Nodes - Joo, Ji Hyeon; Kim, Su Ssan; Son, Byung Ho; Ahn, Seung Do; Jung, Jin Hong; Choi, Eun Kyung; Ahn, Sei Hyun; Lee, Jong Won; Kim, Hee Jeong; Ko, Beom Seok (Cancer research and treatment, 2019)
Axillary lymph node dissection (ALND) may be avoidable for breast cancer patients with 1-2 positive lymph nodes (LN) after breast-conserving therapy. However, the effects of ALND after mastectomy remain unclear because radiation is not routinely used. Herein, we compared the benefits of post-mastectomy ALND versus sentinel node biopsy (SNB) alone for breast cancer patients with 1-3 metastatic LNs. A total of 1,697 patients with pN1 disease who underwent mastectomy during 2000-2015 were identified from an institutional database. Outcomes were compared using the inverse probability of treatment weighted method. Patients who underwent SNB tended to have smaller tumors, a lower histology grade, a lower number of positive LNs, and better immunohistochemical findings. After correcting all confounding factors regarding patient, tumor, and adjuvant treatment, the SNB and ALND groups did not differ in terms of overall survival (OS) and disease-free survival (DFS), distant metastasis and locoregional recurrence. The 10-year DFS and OS rates were 83% and 84%, respectively, during a median follow-up period of 93 months. ALND did not improve post-mastectomy survival outcomes among patients with N1 breast cancer, even after adjusting for all histopathologic and treatment-related factors.